Microsoft Office Professional 2010 step by step - Cox, Joyce, 1946-; Lambert, Joan.; Frye, Curtis, 1968- (Redmond, Wash. : Microsoft ; New Delhi : PHI Learning Pvt. Ltd., 2011)
Presents a guide to Office Professional 2010, describing such tasks as creating documents, spreadsheets, and slide presentations, managing email, and organizing notes, covering the Microsoft programs Word, Excel, Access, OneNote, Publisher, Outlook, and PowerPoint.
Microsoft Office Professional 2010. Explore Office 2010; Work with files -- Microsoft Word 2010. Edit and proofread text; Change the look of text; Organize information in columns and tables; Add simple graphic elements; Preview, print, and distribute documents -- Microsoft Excel 2010. Set up a workbook; Work with data and Excel tables; Perform calculations on data; Change workbook appearance; Focus on specific data by using filters -- Microsoft PowerPoint 2010. Work with slides; Work with slide text; Format slides; Add simple visual enhancements; Review and deliver presentations -- Microsoft OneNote 2010. Explore OneNote 2010; Create and configure notebooks; Create and organize notes -- Microsoft Outlook 2010. Send and receive e-mail messages; Store and access contact information; Manage scheduling; Track tasks -- Microsoft Access 2010. Explore an Access 2010 database; Create databases and simple tables; Create simple forms; Display data -- Microsoft Publisher 2010. Get started with Publisher 2010; Create visual interest; Create colorful cards and calendars.
Includes index.
Keywords: Microsoft Office; Microsoft Office (Computer software); Business -- Computer software